2-chloro-1-(3-mesityl-3-methylcyclobutyl)ethanone - Demir, S; Dinçer, M; Çukurovah, A; Yilmaz, I (Int Union Crystallography, 2006)
The title compound, C16H21ClO, has a non-planar configuration. The crystal packing is mainly stabilized by intramolecular C-H (...) O hydrogen-bonding interactions.